On a Whitham-Type Equation - Sakovich, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
The Hunter-Saxton equation and the Gurevich-Zybin system are considered as two mutually non-equivalent representations of one and the same Whitham-type equation, and all their common solutions are obtained exactly.